Analisis Bauran Pemasaran Untuk Meningkatkan Pendapatan Usahatani Karmel Bawang Merah Didesa Pailelang - Emirensiana Latuan; Didiana Yuarita Molebila; Yulius Nixon Tena (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
The research was carried out in Pailelang Village, Southwest Alor District to find out the product, price, location and promotion as well as the income of shallot farmers in Pailelang Village, Southwest Alor District. The data used in the form of primary data sourced from farmers. The analytical tool used is descriptive analysis with average calculations, while to find out income, t-test analysis is used. The results of the analysis show that the product and price variables simultaneously have a significant and positive relationship to the income of shallots in Pailelang village. Partial analysis, promotion and location variables have no significant positive effect on the income of shallot farmers in Pailelang village.